2006
DOI: 10.1292/jvms.68.783
|View full text |Cite
|
Sign up to set email alerts
|

Drop of Egg Production in Chickens by Experimental Infection with an Avian Metapneumovirus Strain PLE8T1 Derived from Swollen Head Syndrome and the Application to Evaluate Vaccine

Abstract: ABSTRACT. Decreases in egg production and increased incidence of abnormal eggs due to malformation of egg shells were observed in specific pathogen free (SPF) 173-day-old laying hens inoculated intravenously with an avian metapneumovirus (aMPV) strain PLE8T1. This strain was derived from an isolate from broiler birds exhibiting swollen head syndrome (SHS). Some SPF birds inoculated with the virus showed, slight diarrhea without any respiratory symptoms. Thus, the PLE8T1 strain was used as a challenge virus to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In turkeys, it causes turkey rhinotracheitis and it is involved in a disease called swollen head syndrome in chickens. In young turkeys, signs such as ocular and nasal discharge, sneezing, coughing and swelling of the infraorbital sinuses may be observed (Jirjis et al, 2004;Sugiyama et al, 2006). The respiratory signs in aMPV-mono-infected chickens are normally less clear and milder than in turkeys (Lu et al, 1994;Banet-Noach et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In turkeys, it causes turkey rhinotracheitis and it is involved in a disease called swollen head syndrome in chickens. In young turkeys, signs such as ocular and nasal discharge, sneezing, coughing and swelling of the infraorbital sinuses may be observed (Jirjis et al, 2004;Sugiyama et al, 2006). The respiratory signs in aMPV-mono-infected chickens are normally less clear and milder than in turkeys (Lu et al, 1994;Banet-Noach et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…aMPV causes turkey rhinotracheitis (TRT), an acute respiratory tract infection in turkeys of all ages. The virus is also associated with swollen head syndrome (SHS) in ______________________ broilers and broiler breeders (7) and egg production losses in layers (8). In recent years, outbreaks of respiratory disease have been increased in poultry farms in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…aMPV causes turkey rhinotracheitis, an acute respiratory tract infection in turkeys of all ages. The virus is also associated with swollen head syndrome (SHS) in broilers and broiler breeders (O'Brien, 1985;Wyeth et al, 1987;Pattison et al, 1989;Jones et al, 1991;Gough et al, 1994) and egg production losses in layers (Cook et al, 1996(Cook et al, , 2000Sugiyama et al, 2006). It has been reported that chicken aMPV isolates are antigenically closely related to turkey isolates (Cook et al, 1993a), but in previous investigations aMPV isolates from turkeys did not induce clinical signs in chickens (Gough et al, 1988;Buys et al, 1989b).…”
Section: Introductionmentioning
confidence: 99%